2013
DOI: 10.3389/fonc.2013.00212
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Research on “Lymphomas: Role of Molecular Imaging for Staging, Prognostic Evaluation, and Treatment Response”

Abstract: Lymphomas are heterogeneous but potentially curable group of neoplasms. Treatment of lymphomas has rapidly evolved overtime with significant improvement in the cure rate and reductions in treatment-related toxicities. Despite excellent results, treatment programs are continued to be developed to achieve better curative and safety profiles. In these patients individualized therapy schemes can be devised based on a well-defined risk categorization. The therapy efficacy can be increased early during therapy in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 122 publications
0
14
1
1
Order By: Relevance
“…This proposal is distinct from those of Khan et al [14], and Berthet et al [15], in that, in PET/CT negative cases, the former precludes BMB, while the latter considers it an option; therefore, according to our data, 10% of patients will be understaged with those approaches. In addition, it is distinct from those proposed by Mittal et al and Kostakoglu et al, in that they advise BMB in positive PET/CT, which is clinically unnecessary according to our data [24,25].…”
Section: Discussioncontrasting
confidence: 81%
“…This proposal is distinct from those of Khan et al [14], and Berthet et al [15], in that, in PET/CT negative cases, the former precludes BMB, while the latter considers it an option; therefore, according to our data, 10% of patients will be understaged with those approaches. In addition, it is distinct from those proposed by Mittal et al and Kostakoglu et al, in that they advise BMB in positive PET/CT, which is clinically unnecessary according to our data [24,25].…”
Section: Discussioncontrasting
confidence: 81%
“…4,12,23,24 Even though PET/CT imaging has been widely studied in lymphomas and in breast cancer, there is a lack of literature about the role of PET/CT in the diagnosis of phyllodes tumors, because of the rarity of this disease. [25][26][27][28] In 1996, Holle et al first showed an intense 18 F-FDG uptake in a rapidly growing phyllodes tumor. 29 Two years later, Bakheet and colleagues reported the case of a 22-year-old woman with an 18 F-FDG avid focus in the right breast corresponding to the local recurrence of a cystosarcoma phyllodes.…”
Section: Discussionmentioning
confidence: 99%
“…In abdominal lymphoma, CECT may be helpful in differentiating lymph nodes from collapsed bowel loops and vessels; in head and neck lymphoma, it may be useful to differentiate physiologic uptake from enlarged cervical lymph nodes. A diagnostic CT scan is required where precise measurements of involved lymph nodes are needed (44). …”
Section: The Role Of Imaging In the Management Of Dlbclmentioning
confidence: 99%